Microstructural changes in the spinal cord of adults with cerebral palsy. (14th March 2021) - Trevarrow, Michael P; Baker, Sarah E; Wilson, Tony W; Kurz, Max J
Abstract : Aim: To quantify the microstructural differences in the cervical‐thoracic spinal cord of adults with cerebral palsy (CP). Method: Magnetic resonance imaging of the proximal spinal cord (C6–T3) was conducted on a cohort of adults with CP ( n =13; mean age=31y 11mo, standard deviation [SD] 8y 7mo; range=20y 8mo–47y 6mo; eight females, five males) and population norm adult controls ( n =16; mean age=31y 4mo, SD 9y 9mo; range=19y 4mo–49y 5mo; seven females, nine males). The cross‐sectional area (CSA) of the spinal cord, gray and white matter, magnetization transfer ratio (MTR), and fractional anisotropy of the cuneatus and corticospinal tracts were calculated. Results: The total spinal cord CSA and proportion of the spinal cord gray matter CSA were significantly decreased in the adults with CP. The corticospinal tracts' MTR was lower in the adults with CP. Individuals that had reduced gray matter also tended to have reduced MTR in their corticospinal tracts ( r =0.42, p =0.029) and worse hand dexterity clinical scores ( r =0.53, p =0.004). Interpretation: These results show that there are changes in the spinal cord microstructure of adults with CP. Ultimately, these microstructural changes play a role in the extent of the hand sensorimotor deficits seen in adults with CP. What this paper adds Adults with cerebral palsy (CP) have a reduced spinal cord cross‐sectional area (CSA). Spinal cord gray matter is reduced in adults with CP. Spinal cord CSA is associated with hand dexterity. Magnetization transfer ratio of corticospinal tracts was lower in adults with CP. What this paper adds: Adults with cerebral palsy (CP) have a reduced spinal cord cross‐sectional area (CSA). Spinal cord gray matter is reduced in adults with CP. Spinal cord CSA is associated with hand dexterity. Magnetization transfer ratio of corticospinal tracts was lower in adults with CP. This article is commented on by Cohen‐Adad on page 896 of this issue. Video Podcast: https://www.youtube.com/watch?v=z0vvrsNitJM Cambios microestructurales de la médula espinal en adultos con parálisis cerebral: Objetivo: Cuantificar las diferencias microestructurales en la médula espinal cérvico‐torácica de adultos con parálisis cerebral (PC). Método: Se realizó una resonancia magnética de la médula espinal proximal (C6‐T3) en una cohorte de adultos con PC (n = 13; edad media = 31 años 11 meses, desviación estándar [DE] 8 años 7 meses; rango = 20 años 8 meses – 47 años 6 meses; ocho mujeres, cinco hombres) y controles de población adulta normal (n = 16; edad media = 31 años 4 meses, DE 9 años 9 meses; rango = 19 años 4 meses – 49 años 5 meses; siete mujeres, nueve hombres). Se calculó el área de sección transversal (CSA, siglas en ingles) de la médula espinal, la sustancia gris y blanca, la tasa de transferencia de magnetización (MTR, siglas en ingles) y la anisotropía fraccionada de los tractos cuneiforme y corticoespinal. Resultados: El CSA total de la médula espinal y la proporción del CSA de la sustancia gris de la médula espinal disminuyeron significativamente en los adultos con PC. La MTR de los tractos corticoespinales fue menor en los adultos con PC. Los individuos que habían reducido la materia gris también tendían a tener una reducción de la MTR en sus tractos corticoespinales (r = 0, 42, p = 0, 029) y peores puntuaciones clínicas de destreza manual (r = 0, 53, p = 0, 004). Interpretación: Estos resultados muestran que hay cambios en la microestructura de la médula espinal de los adultos con parálisis cerebral. En última instancia, estos cambios microestructurales influyen en la extensión de los déficits sensoriomotores de la mano que se observan en adultos con parálisis cerebral. Mudanças microestruturais na medula espinhal de adultos com paralisia cerebral: Objetivo: Quantificar as diferenças microestruturais na medula espinhal cérvico‐torácica de adultos com paralisia cerebral (PC). Método: Imagem por ressonância magnética da medula espinhal proximal (C6–T3) foi realizada em uma coorte de adultos com ( n =13; média de idade=31a 11m, desvio padrão [DP] 8a 7m; variação=20a 8m–47a 6m; oito do sexo feminino, cinco do sexo masculino) e adultos controle como população normativa ( n =16; média de idade =31a 4m, DP 9a 9m; variação=19a 4m–49a 5m; sete do sexo feminino, nove do sexo masculino). A área de secção transversa (AST) da medula espinhal, substância cinzenta e branca, a taxa de transferência de magnetização (TTM) e a anisotropia fractional dos tratos cuneiforme e córtico‐espinhal foram calculados. Resultados: A AST total da da medula espinhal e a proporção da AST da medula espinhal com substância cinzenta foram significativamente menores nos adultos com PC. A TTM do trato córtico‐espinhal foi menor nos adultos com PC. Indivíduos que tinha substância cinzenta reduzida também tenderam a ter TTR reduzida nos tratos córtico‐espinhais ( r =0, 42, p =0, 029) e pior escores clínicos de destreza manual ( r =0, 53, p =0, 004). Interpretação: Estes resultados mostram que há mudanças na microestrutura da medula espinhal de adultos com PC. Estas mudanças microestruturais desempenham um papel nos déficits sensório‐motores da mão vistos em adultos com PC.